Pengaruh Stabilitas Keamanan Indo-Pasifik melalui AOIP terhadap Ketegangan China-Taiwan dalam Penyelesaian Sengketa Maritim - Fahmi, Muh Nurfaiz; Nugraha, Imam Fadhil (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2025)
This research analyzes ASEAN’s role through the ASEAN Outlook on the Indo-Pacific (AOIP) in responding to China–Taiwan tensions that threaten regional maritime security. AOIP promotes cooperation based on inclusivity, ASEAN centrality, and respect for international law. Despite broad support from major partners like the U.S. and Japan, AOIP’s effectiveness remains limited due to its non-binding nature and ASEAN’s cautious stance toward China’s assertiveness. Using a descriptive-analytical method, the research finds that AOIP lacks strategic tools to prevent escalation or address real-time threats. The study recommends strengthening ASEAN’s collective capacity through early warning mechanisms and deeper multilateral cooperation. AOIP must evolve beyond a normative framework into a proactive platform capable of supporting regional stability and managing power rivalries in the Indo-Pacific.